Alienation and obligation: religion and social change in Samoa - Thornton, Alec (Asia Pacific viewpoint, 2010)
This paper will explore social change in contemporary Samoan society with respect to the traditional expectations of the church and kinship conflicting with the modern needs of an urbanising population. In the Samoan way of life - the fa'aSamoa - religion, matai (chiefly system) and reciprocal 'gift-giving' kinship arrangements among the aiga (extended family) are fundamental and closely related elements. However, pressures from continued integration into the global economy, the importance of remittance income and related migration of well-educated and highly skilled Samoans overseas are presenting several challenges to the strongly held traditions of kinship and church obligations. Among these challenges, low-income households are increasingly placing the material well-being of the immediate household first, thus 'opting out' of the culturally defined primary obligation to the church and risk alienation from beneficial familial ties. As a result, settlement patterns are shifting towards leaseholds in urbanising Apia, with consequences, we will speculate, that may have deeper cultural implications. Our research revealed that the church has been slow to accept that, increasingly, Samoans are seeking relief from hardships that spirituality alone cannot address. However, given its influence, strengths and resources, the church is well positioned to take a lead role in facilitating opportunities for 'bottom-up', alternative development in Samoa, as well as providing lessons for church-led participatory approaches in the Pacific Island Region. (Asia Pac Viewp/GIGA)